Postmortem conception of a dead husband’s semen as a particular example of medically assisted procreation - Marszelewski, Michał (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2013)
The paper covers issues concerned with the postmortem conception of a dead husband’s semen as a particular example of medically assisted procreation. For this purpose it examines the possible varieties of postmortem conception with legal and factual circumstances of entities who are participating in such a procedure. Ethical aspects and questions which arise from allowing or prohibiting postmortem conception are also described. The paper presents important issues which postmortem conception causes in many areas of law, including an understanding of the principle of the best interests of the child. The paper then explains the legal situation of a child born as a result of postmortem conception under Polish law. It contains important foreign and Polish case law and cites the most important opinions of experts in the discussed topic.